2013
DOI: 10.1111/jam.12315
|View full text |Cite
|
Sign up to set email alerts
|

CpG7909 adjuvant enhanced immunogenicity efficacy in mice immunized with ESAT6-Ag85A fusion protein, but does not confer significant protection against Mycobacterium tuberculosis infection

Abstract: Aims: This study aimed to investigate the ability of CpG7909 adjuvant to enhance immunogenicity and protective efficacy of a subunit vaccine composed of ESAT6-Ag85A fusion protein (Pe685a) of Mycobacterium tuberculosis. Methods and Results: ELISA was used to detect specific antibody and IFN-c expression in sera; ELISPOT, to detect IFN-c expression in splenocytes; MTT assay and FACS, to detect T-lymphocytes proliferation in spleens; and RT-PCR, to detect cytokines expression in lungs of mice after immunization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In our previous work, CpG7909 was used as adjuvant of an anti-tuberculosis subunit vaccine. CpG7909 was able to enhance Th1-type immunity induced by subunit vaccine [38]. In the current work, it was determined that, as immunostimulant, CpG7909 induced M1 polarization of U937 cells, however, M. tb infection suppressed CpG7909-evoked M1 polarization.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our previous work, CpG7909 was used as adjuvant of an anti-tuberculosis subunit vaccine. CpG7909 was able to enhance Th1-type immunity induced by subunit vaccine [38]. In the current work, it was determined that, as immunostimulant, CpG7909 induced M1 polarization of U937 cells, however, M. tb infection suppressed CpG7909-evoked M1 polarization.…”
Section: Discussionmentioning
confidence: 77%
“…We have previously reported that CpG7909 was able to enhance the ability of subunit vaccine to induced Th1-type immunity, however, CpG7909 was not able to improve its protective effects against M. tb infection [38]. The negative regulatory role of IRAK-M might contribute to this phenomenon.…”
Section: Discussionmentioning
confidence: 92%
“…The adjuvants used for enhancing the immunogenicity and protective efficacy of Ag85A are DDA, CpG7909. Studies show that CpG7909 is able to enhance the immunological effects of Ag85A (Hu et al, 2013), but it does not confer significant protective efficacy against infection with M. tuberculosis. In contrast, Brandt's research has shown that DDA-MPL can induce similarly high levels of immunity as BCG (Brandt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have been conducted with CPG 7909-adjuvanted vaccine candidates against diseases caused by Plasmodium , Pseudomonas , and Mycobacterium species. 1-3 These studies showed induction of an innate cellular and humoral immune response, consistent with TLR9 activation, characterized by the production of pro-inflammatory cytokines which in turn may enhance the vaccine efficacy. 4 Similarly, CPG 7909 enhanced immunogenicity and efficacy of anthrax vaccines in mice, guinea pigs, and nonhuman primates.…”
Section: Introductionmentioning
confidence: 89%